The relative discriminatory power of a selection of neuropsychological tests in Alzheimer's disease - Aronson, Steven (Rhodes University, Faculty of Humanities, Department of Psychology, 1994)
KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Alzheimer's disease -- Physiological aspects; Neuropsychological tests